Study on growth, potential utility and N.P.P. of a submerged aquatic plant Hydrilla verticillata Casp. - Patel, Devendra Kumar; Kanungo, V K (Journal of Experimental Sciences, 2012)
Hydrilla verticillata Casp is a rooted submerged aquatic plant belonging to the family Hydrocharitaceae. It is distributed in aquatic bodies over the world. Hydrilla verticillata Casp affect the aquatic system positively or by negatively based on their density in aquatic bodies. Specific growth pattern, Physiology and mode of vegetative propagation etc. help Hydrilla verticillata Casp to adopt in various types of fresh water environment. Aquatic plants are important for maintaining life system in water bodies and also useful for nutrient recycling. A wide ecological impact of aquatic plants in water has been recorded by the researchers in the world. The aim of the present study was to examine the growth and estimation of NPP of Hydrilla verticillata Casp in an artificial water tank and plastic tubs respectively. Findings of the experiments are discussed furthermore.